Determinants and effects or consequences of internal HIV-related stigma among people living with HIV in Morocco - Amal Ben Moussa; Rosemary M. Delabre; Virginie Villes; Mohammed Elkhammas; Aziza Bennani; Lahoucine Ouarsas; Hind Filali; Kamal Alami; Mehdi Karkouri; Daniela Rojas Castro (BMC, 2021)
Abstract Background HIV-related stigma and discrimination constitute a barrier to different intervention programs. Unlike external stigma, internal stigma is not well explored in in the Middle East and North African countries, while grasping this particular form of stigma is essential to limit its effects. The present study aims to measure internal stigma effects and to identify factors associated with this kind of stigma not yet documented among people living with HIV (PLHIV) in Morocco. Methods The PLHIV Stigma Index questionnaire (adapted and translated into French and Moroccan Arabic dialect "darija") was used to collect information regarding the stigma and discrimination experienced by PLHIV across 8 cities in Morocco (September-October 2016). A randomly drawn cluster of 10 PLHIV, consisting of 5 men and 5 women, was drawn at each participating medical care center to achieve a nationally representative sample of PLHIV. Fifteen interviewers living with HIV and five supervisors were selected and trained to administer the questionnaire. An internal stigma score (range: 0-7), was calculated based on seven negative feelings/ beliefs. Negative binomial regression was used to identify characteristics associated with the internal stigma score. Results Among 626 PLHIV, internal stigma was reported by 88.2%. The median [IQR] internal stigma score was 4 [2-5]. Regarding internal stigma, 51% avoided going to the local clinic when needed and 44% chose not to attend social gatherings. Belonging to at least one key population (aIRR [95%CI] = 1.15 [1.03; 1.28]), experiencing discriminatory reactions from family following HIV status disclosure (1.28 [1.11; 1.49]), avoiding HIV services for fear of stigmatization by staff (1.16 [1.05; 1.28]) and being denied health services because of HIV status (1.16 [1.03;1.32]), are among the factors significantly associated with an increase of the internal stigma score. Conclusions Internal stigma is high among Moroccan PLHIV and significantly impacting their life decisions and their healthcare access. Multi-level interventions are needed to address internal stigma experienced by PLHIV in Morocco.